L-amino acid oxidase 1 in sperm is associated with reproductive performance in male mice and bulls. Issue 5 (16th February 2021) - Zhang, Haolin; Liu, Hong; Kataoka, Sachi; Kinukawa, Masashi; Uchiyama, Kyoko; Kambe, Jun; Watanabe, Gen; Jin, Wanzhu; Nagaoka, Kentaro
Abstract: Sperm quality is an important indicator of male fertility, and a suitable biomarker enables the selection of high-quality spermatozoa. We previously found that L-amino acid oxidase encoded by the L-amino acid oxidase 1 ( Lao1 ) gene exerts biological roles in the mammary gland and brain by converting specific L-amino acids into keto acids, ammonia, and hydrogen peroxide (H2 O2 ). Here, we describe the role of Lao1 in male reproduction. Lao1 -deficient ( Lao1 −/− ) male mice generated fewer pregnant embryos and pups as well as lower ratios of fertilized oocytes and even ovulated number was not different, suggesting that male subfertility caused the smaller litters. We found that LAO1 expressed in acrosomes is associated with high malformation ratios and low viability of Lao1 −/− sperm. Wild-type (WT) sperm produced more H2 O2 than Lao1 −/− sperm, and 10 μM H2 O2 restored knockout (KO) sperm viability in vitro. In addition, the sperm ratio of induced acrosome reaction was higher in WT than in Lao1 −/− sperm incubated with the calcium ionophore A23187. Moreover, LAO1 expression was abundant in bovine sperm with high fertilization ratios. We concluded that LAO1 localized in the sperm acrosome influences sperm viability and morphology as well as the acrosome reaction, and that LAO1- deficient sperm might cause male subfertility. Thus, LAO1 might serve as a novel marker for selecting high-quality spermatozoa, especially for livestock reproduction. Abstract : LAO1 localized in the sperm acrosome may influence sperm viability and acrosome reaction by metabolizing L-amino acid to produce H2 O2 .